The Development of the Conception of Beauty in Lithuanian Idealistic Aesthetics (1918-1940) - Andriuškevičius, Alfonsas (Problemos, 1988)
A. Jakštas, S. Šalkauskis, A. Viskantas and J. Grinius were the main four authors who worked out the conception of beauty. Its basic features are idealistic objectivism and unhistoric approach. The four differed in the understanding of the principles of beauty as well as in the interpretation of its embodiment. In its development the conception made a turn from radical objectivism to subjectivization. However, the latter was to a great extent illusory because of the unhistorical treatment of the subject.